An environmental scan of the immigrant-serving sector in Calgary: core-periphery model - Gurleen Kaur Matharu; Jenalyn M. Ormita; Katerina Palova; Odessa Gonzalez Benson (Discover Global Society)
Abstract The local context of social services plays a crucial role in the transition and integration of newcomers in new places of settlement. This paper presents a summary of findings from an environmental scan that sought to examine the organizational and service landscape within the immigrant-serving sector, focusing on Calgary, Alberta as the site of study. As findings, we conceptualize Calgary’s immigrant-serving sector via a core-periphery model, whereby a small set of core organizations and service areas are prioritized, rather than more interconnections and diversity. Our preliminary empirical findings point to the sector’s strengths, but also the potential for accessing resources and collaborations that are still untapped. As an exploratory method and first step in a larger practice-based project, this environmental e-scan aims to provide an initial, approximate analysis to then prompt and raise questions for deeper empirical research and applications to practice in the future.